Essential Song: Three Decades of Northern Cree Music - Whidden, Lynn (Wilfrid Laurier University Press, 2007)
A pack that contains a book and a CD. The book presents an outline of Cree musical history and a contribution to ethnomusicology, social history, and Aboriginal studies. The CD contains over 80 Cree hunting songs.

"Gnaah" and the Trout Song - Whidden, Lynn (Proceedings of Eighth Workshop on the Structure and Constituency of Languages of America, 2003)